Does electrical activity in fungi function as a language? - Blatt, Michael R.; Pullum, Geoffrey K.; Draguhn, Andreas; Bowman, Barry; Robinson, David G.; Taiz, Lincoln (Fungal ecology, 2024)
All cells generate electrical energy derived from the movements of ions across membranes. In animal neurons, action potentials play an essential role in the central nervous system. Plants utilize a variety of electrical signals to regulate a wide range of physiological processes, including wound responses, mimosa leaf movements, and cell turgor changes, such as those involved in stomatal movements. Although fungal hyphae exhibit electrical fluctuations, their regulatory role(s), if any, is still unknown. In his paper “Language of fungi derived from their electrical spiking activity”, Andrew Adamatzky, based on a quantitative analysis of voltage fluctuations in fungal mycelia, concludes that the patterns of electrical fluctuations he detects can be grouped into “words” analogous to those found in human languages. He goes on to speculate that this “fungal language” is used “to communicate and process information” between different parts of the mycelium. Here we argue on methodological grounds that the presumption of a fungal language is premature and unsupported by the evidence presented, that the voltage fluctuations he detects are likely to originate as nonbiological noise and experimental artifacts, and that the measured electrical patterns show no similarity to any properties of human language.